2002
DOI: 10.1182/blood-2001-12-0159
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid for the prevention of hepatic complications in allogeneic stem cell transplantation

Abstract: The role of ursodeoxycholic acid (UDCA) in the prevention of hepatic complications after allogeneic stem cell transplantation was studied in a prospective randomized open-label multicenter trial. A total of 242 patients were allocated to receive (n ‫؍‬ 123) or not to receive (n ‫؍‬ 119) UDCA in the dose of 12 mg/kg/d orally from the day preceding the conditioning until day 90 after transplantation. In the UDCA-treated group a significantly smaller proportion of patients developed a serum bilirubin level exceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(176 citation statements)
references
References 29 publications
3
168
0
2
Order By: Relevance
“…[24][25][26][27][28] In this population, neither heparin, nor ursodexosycholic acid administration appeared to minimize the risk of HVOD compared to that reported in other series. However, in the present series these drugs were not prospectively evaluated by randomization.…”
Section: Discussionmentioning
confidence: 68%
“…[24][25][26][27][28] In this population, neither heparin, nor ursodexosycholic acid administration appeared to minimize the risk of HVOD compared to that reported in other series. However, in the present series these drugs were not prospectively evaluated by randomization.…”
Section: Discussionmentioning
confidence: 68%
“…A randomized prospective clinical trial in adult patients receiving myeloablative conditioning found that SCT recipients treated with ursodeoxycholic acid during the early phase after transplantation had lower risk of liver injury, aGVHD and NRM than patients not receiving ursodeoxycholic acid. 43 However, another randomized study did not find any survival benefit of the combination of heparin and ursodeoxycholic acid compared with heparin alone. 44 More recently, a meta-analysis including 824 patients from 6 studies showed a lower risk of VOD and NRM in patients receiving ursodeoxycholic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hepatic cGVHD meeting the following criteria were entered into this study: ALP or g-GTP elevated more than twice the upper normal limits and improved less than 10% by UDCA and immunosuppressants (PSL and/or CsA); negative for anti-hepatitis C virus antibody, hepatitis B virus surface antigen and CMV antigen; no evidence of non-alcoholic fatty liver disease and other biliary tract diseases on ultrasonography and/or computerized tomography (CT). Furthermore, 12 patients (non-BF group) treated without BF from 1997 to 2000 in our hospital were selected retrospectively so that they were age and sex matched with the BF group (Table 1, patients [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…A recent report of a large, randomized, multicenter trial revealed that prophylactic UDCA administration was effective in preventing severe acute GVHD after allo-SCT and improved survival, 11 but there was no difference in cGVHD. Chronic nonsuppurative destructive cholangitis is a common pathological feature of cGVHD and PBC, 16 where the bile duct epithelial cells are the targets of immunological injury.…”
Section: Case Reportsmentioning
confidence: 99%
See 1 more Smart Citation